2019
DOI: 10.2174/1574887114666190729143742
|View full text |Cite
|
Sign up to set email alerts
|

Yoga Protocol for Cancer Patients: A Systematic Exploration of Psychophysiological Benefits

Abstract: Background: Several studies report that practicing Yoga may lead to numerous psychophysiological benefits in patients undergoing treatment for cancer. Moreover, it may result in an effective alternative for coping with sleep disturbances, anxiety, depression and fatigue symptoms. A study based on the “Yoga in Oncology” project of the Foundation Poliambulanza was carried out, and it was designed to explore the benefits of Yoga, therefore corroborating Yoga as a therapeutic activity that can have a beneficial im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Reviews of a wide range of yoga practices suggest that they can reduce the impact of exaggerated stress responses and may be helpful for both anxiety and depression. [ 11 12 13 14 20 21 ] One randomized control trial on yoga's effect on cancer patients’ anxiety showed that yoga sessions for eight weeks significantly reduced perceived depression and anxiety. [ 21 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reviews of a wide range of yoga practices suggest that they can reduce the impact of exaggerated stress responses and may be helpful for both anxiety and depression. [ 11 12 13 14 20 21 ] One randomized control trial on yoga's effect on cancer patients’ anxiety showed that yoga sessions for eight weeks significantly reduced perceived depression and anxiety. [ 21 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 12 13 14 20 21 ] One randomized control trial on yoga's effect on cancer patients’ anxiety showed that yoga sessions for eight weeks significantly reduced perceived depression and anxiety. [ 21 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation